2011
DOI: 10.1289/ehp.1103564
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Urban Particulate Air Pollution, Traffic Noise, and Arterial Blood Pressure

Abstract: Background: Recent studies have shown an association of short-term exposure to fine particulate matter (PM) with transient increases in blood pressure (BP), but it is unclear whether long-term exposure has an effect on arterial BP and hypertension.Objectives: We investigated the cross-sectional association of residential long-term PM exposure with arterial BP and hypertension, taking short-term variations of PM and long-term road traffic noise exposure into account.Methods: We used baseline data (2000–2003) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
174
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(192 citation statements)
references
References 35 publications
12
174
2
4
Order By: Relevance
“…31 These three hypotheses provide contextual background to evaluate the experimental and clinical findings describing the extrapulmonary effect of particulate matter air pollution, where it has been reported that exposure to elevated levels of PM 2.5 is associated with increased inflammatory mediators (including TNF-a, IL-6, and plasminogen activator inhibitor-1), oxidative stress, [32][33][34] increased atherosclerotic plaque area, and exaggerated vasoconstrictor responses to phenylephrine and serotonin. 35 Evidence suggests that increased PM 2.5 concentrations are associated with significant decrease in flow-mediated dilatation, 36,37 increases in systolic BP and pulse pressure, [38][39][40] and disturbances in the hypothalamic-pituitary-adrenal axis. 41 Emerging evidence also suggests that exposure to ambient air pollutants can lead to metabolic disturbances, including glucose intolerance, decreased insulin sensitivity, higher blood lipid concentrations, weight gain, and increased risk of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…31 These three hypotheses provide contextual background to evaluate the experimental and clinical findings describing the extrapulmonary effect of particulate matter air pollution, where it has been reported that exposure to elevated levels of PM 2.5 is associated with increased inflammatory mediators (including TNF-a, IL-6, and plasminogen activator inhibitor-1), oxidative stress, [32][33][34] increased atherosclerotic plaque area, and exaggerated vasoconstrictor responses to phenylephrine and serotonin. 35 Evidence suggests that increased PM 2.5 concentrations are associated with significant decrease in flow-mediated dilatation, 36,37 increases in systolic BP and pulse pressure, [38][39][40] and disturbances in the hypothalamic-pituitary-adrenal axis. 41 Emerging evidence also suggests that exposure to ambient air pollutants can lead to metabolic disturbances, including glucose intolerance, decreased insulin sensitivity, higher blood lipid concentrations, weight gain, and increased risk of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Those who have done so found that excess risks of air pollution in the proximity of roads generally remained after adjustment for noise for cardiovascular mortality (Beelen et al, 2008a;Gan et al, 2012), hypertension and diabetes mellitus (Coogan et al, 2012), hypertension (Fuks et al, 2011;Sørensen et al, 2012), and cognitive performance of primary schoolchildren (van Kempen et al, 2012). Therefore, these studies show effects of air pollution that cannot be explained by noise.…”
Section: Rationalementioning
confidence: 95%
“…41 Oxidative stress may also increase the circulation of activated inflammatory cytokines, which may subsequently induce endothelial dysfunction, lead to an imbalance in vascular homeostatic response, and result in total peripheral resistance and a fixation of evaluated blood pressure. 40,42 PM may also elevate blood pressure by inducing autonomic nervous system imbalance and vasoconstriction. 24 In addition, PM exposure can also reduce daytime sodium excretion and blunt the normal nocturnal reduction in blood pressure.…”
mentioning
confidence: 99%